EPAS1 Variations and Hematological Adaptations to High-Altitude Hypoxia in Indigenous Goats in Yunnan Province, China - Li Zhu; Lin Tang; Yunong Zhao; Shanshan Li; Xiao Gou; Weidong Deng; Xiaoyan Kong (Animals)
The EPAS1 gene plays a central role in hypoxia adaptation in high-altitude animals. Using over 400 blood samples from goats across elevations in Yunnan (500–3500 m), this study examined hematological traits, genetic polymorphisms, and protein structure. Red blood cell (RBC) and hemoglobin (HGB) levels increased significantly with altitude (p < 0.05), reflecting improved oxygen transport. A non-synonymous SNP (g.86650 A>T, p.Gln556Leu) exhibited adaptive selection, with the T allele frequency rising at higher altitudes (p < 0.05). At 2500 m, TT genotype goats showed significantly higher RBC and HGB levels than AA genotypes (p < 0.05). Protein modeling revealed structural instability caused by the polymorphism, highlighting its role in enhancing hypoxia adaptation. These findings provide a foundation for improving high-altitude livestock genetics.